Determinación de presencia de Pseudomonas Aeruginosa y medidas de control en aguas termales (2017)
In Colombia, thermal waters have regulations subject to what is established by the Ministry of Health and Social Protection, does not have a regulation that establishes The minimum quality standards and control activities to be carried out in Thermal waters to ensure optimum conditions at the time of use, without However, the law on hot springs is currently in draft law (Law 62 of 2015). Given the lack of regulations in Colombia, the existing standards were consulted In countries such as Spain, Chile, Cuba and others in relation to the microbiological quality of Thermal water, taking as reference the pathogen of Pseudomonas aeruginosa, as well as Such as control measures in facilities where swimming pools are provided Of thermal waters.